2016
DOI: 10.1136/bmj.i5663
|View full text |Cite
|
Sign up to set email alerts
|

Allocation concealment in randomised controlled trials: are we getting better?: Table 1

Abstract: Laura Clark and colleagues assess the allocation concealment methods in a sample of randomised controlled trial publications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Similar to blinding, allocation concealment is an important element to control bias in a clinical trial. A study examining a sample of RCTs published in major medical journals in 2015 found that nearly 40% of these studies did not report satisfactory methods for allocation concealment (40). However, improvements have been noted as far as reporting trends are concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to blinding, allocation concealment is an important element to control bias in a clinical trial. A study examining a sample of RCTs published in major medical journals in 2015 found that nearly 40% of these studies did not report satisfactory methods for allocation concealment (40). However, improvements have been noted as far as reporting trends are concerned.…”
Section: Discussionmentioning
confidence: 99%
“…The randomisation permits the use of the probability theory to express the likelihood of chance as a source for the differences of an outcome . The allocation concealment refers to separate the act of randomisation from the person recruiting participants and is dependent on the method of sequence generation, as well as, the concealment mechanism . A total of seven out of the ten studies described clearly the randomisation and allocation concealment in this systematic review .…”
Section: Discussionmentioning
confidence: 99%
“…Fifty patients were randomly allocated into experimental and control groups (25 patients each) using the sequentially numbered, opaque sealed envelopes method. Where envelopes containing the treatment allocation were opened by the recruiting physician (Clark et al, 2016).…”
Section: Methodsmentioning
confidence: 99%